Emissions taxes under double-sided environmental externalities - Abdul Baki, Ghina (2024)
It is well established that if a polluter exercises market power, the optimal emission tax should be set below the Pigouvian level, i.e., the marginal damage of pollution. In this paper, we show that relying on this intuition can be misleading if pollution is generated by both production and consumption. Specifically, we build a partial equilibrium model based on a monopoly power exerted over a final product, where the production and consumption of this product impose an environmental externality. We find that the first best can be attained by a combination of taxes on pollution from production and consumption, where the tax on the polluting monopoly is set precisely at the Pigouvian level, whereas the tax on (price-taking) consumers is set below the Pigouvian level.